THE CORRELATION BETWEEN CRITICAL THINKING SKILL AND WRITING ARGUMENTATIVE ESSAY ACHIEVEMENT - Wahyuning Prastya, Intan; Soe’oed, Rahmat; Setiawan, Iwan (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
The purpose of this study were (1) to know critical thinking skill of the fifth semester English Department students of Mulawarman University, (2) To know writing argumentative essay achievement of the fifth semester English Department students of Mulawarman University, (3) To find whether there is significant correlation between critical thinking skill and writing argumentative essay achievement of the fifth semester English Department students of Mulawarman University.The design of this study was correlation design. By using random sampling, we took 30 students as our research participants. In getting the data, we used critical thinking test and writing argumentative essay test. Furthermore, the data were analyzed by using IBM SPSS Statistics 21.The findings of this study showed that: (1) The critical thinking skill achievement of the fifth semester English department students of Mulawarman University was poor with the mean score of 51.51; (2) The writing argumentative essay achievement of the fifth semester English department students of Mulawarman University was good with the mean score of 74.42; (3) there is a significant correlation between critical thinking skill and writing argumentative essay achievement of the fifth semester English Department students of Mulawarman University.